NU, SOEKARNO DAN STAAT ISLAM: WACANA NEGARA ISLAM DALAM BERITA NAHDLATOEL OELAMA (BNO) - Najib, Muhammad Ainun (Ahkam: Jurnal Hukum Islam, 2017)
Islamic state once became the central discourse in the ideological debate of the state before and several years after Indonesian independence. Even the discourse of Islamic state has not yet been resolved until now. As one of the religious organizations, in the historical record, Nahdlatul Ulama (NU) was actually supporting the establishment of an Islamic state in Indonesia. Informed from Bi-weekly News of Nahdlatoel Oelama (BNO) published between June 1 to October 15, 1940, NU believed that Islam covers the issue of religion and the world, including politics. Therefore, they rejected Soekarno’s secularism discourse. As a traditionalist Islamic groups, NU involved in the polemics of the state ideology which was often narrated merely by modernist Islamic groups.Keywords: Wacana Negara Islam, NU, Soekarno